2018
DOI: 10.3892/or.2018.6358
|View full text |Cite
|
Sign up to set email alerts
|

Huaier suppresses proliferative and metastatic potential of prostate cancer PC3 cells via downregulation of Lamin�B1 and induction of autophagy

Abstract: Prostate cancer is one of the most common malignancies occurring in males. Although large advances have been made in the pathogenesis of prostate cancer, the development of drugs with high efficacy and low toxicity for the treatment of prostate cancer is urgently needed. Recently, more and more attention has been paid to the antitumor effect of Traditional Chinese Medicine (TCM) worldwide. Trametes robiniophila Murr. (Huaier) has been applied as a type of TCM drug for ~1,600 years. Huaier exhibits excellent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…As summarized in Table 1, TPG-1 contained glucose (Glc), xylose (Xyl), arabinose (Ara), rhamnose (Rha), galactose (Gal), and mannose (Man). Our results showed the presence of six linked types, namely 2,4,6-Me 3 In addition, amino acid analysis showed that the total amino acid content of TPG-1 was 41.20%. There were 17 kinds of amino acids in TPG-1, and the major amino acid was glutamic acid (7.42%), followed by aspartic acid, glycine, arginine, threonine, alanine, proline, and serine.…”
Section: Isolation Purification and Characterization Of The Proteogmentioning
confidence: 50%
See 1 more Smart Citation
“…As summarized in Table 1, TPG-1 contained glucose (Glc), xylose (Xyl), arabinose (Ara), rhamnose (Rha), galactose (Gal), and mannose (Man). Our results showed the presence of six linked types, namely 2,4,6-Me 3 In addition, amino acid analysis showed that the total amino acid content of TPG-1 was 41.20%. There were 17 kinds of amino acids in TPG-1, and the major amino acid was glutamic acid (7.42%), followed by aspartic acid, glycine, arginine, threonine, alanine, proline, and serine.…”
Section: Isolation Purification and Characterization Of The Proteogmentioning
confidence: 50%
“…(Huaier) is a medicinal fungus that has been applied for disease treatment for more than 1600 years in China. Numerous studies have shown that Huaier exhibits good clinical efficacy in the treatment of liver cancer, gastric cancer, prostate cancer, colon cancer, breast cancer, and lung cancer (1)(2)(3)(4). There is evidence that some polysaccharides of Huaier aqueous extract show anti-tumor and immunomodulatory activities.…”
mentioning
confidence: 99%
“…Therefore, elucidating disease-specific gene expression patterns has helped to uncover some of the underlying mechanisms of different diseases [16].When compared to other analytical approaches, WGCNA provides a higher reliability and biological significance due to both genetic modules and clinical parameters being simultaneously examined [17]. Furthermore, WGCNA has been widely used to screen genes associated with pathogenesis or cancer clinical parameters, including lung cancer [18],colon cancer [19],melanoma [20],and osteosarcoma [21]. In the present study, the mainaim was to utilize WGCNA to aid in the identification of key genes associated with HCC development and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that T. robiniophila Murr. could inhibit the cell growth and induce apoptosis in human lung cancer A549, renal cancer 786-O, and prostate cancer PC3 cells (Wu T. et al, 2014; Wei et al, 2018; Yang et al, 2018). Multiple studies have demonstrated that the aqueous extract of T. robiniophila Murr.…”
Section: Anticancer Tcms Through Affecting the Bcl-2/bax Pathwaymentioning
confidence: 99%